2010
DOI: 10.1890/09-2142.1
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved iron supply limits early growth of estuarine mangroves

Abstract: Three mesocosm experiments were performed in an outdoor facility to quantify the responses of five mangrove species grown from seedling to sapling stage to increasing rates of dissolved iron supply. Stem extension and biomass of mangroves were measured in the first two experiments, and in the third experiment, rates of microbial iron reduction were measured in relation to stem extension of two mangrove species. In all experiments, mangrove growth was enhanced by increasing iron supply, although some species sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
3
36
1
Order By: Relevance
“…Our results reveal a low iron resorption efficiency (≤42%) for Avicennia marina in the Central of the Red Sea, about half that for N and P. The comparatively low efficiency in iron resorption, compared to N and P resorption helps explain experimental results reporting that iron additions resulted in significantly taller plants compared with complete fertilizer additions, and consistent with the biogenic nature of the sediments in the Red Sea (Almahasheer et al, 2016b), similar to the iron deficiency of seagrass growing above carbonate sediments reported in the Mexican Caribbean (Duarte et al, 1995). These results also support the findings of a mesocosm experiment (Alongi, 2010) reporting that mangroves growth in some forests may be limited by the rate at which iron is solubilized by iron-reducing bacteria. Particularly when considering the high sediment Fe stock in this study of 1 Kg m −2 compared to around 0.1 Kg m −2 for N and P respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results reveal a low iron resorption efficiency (≤42%) for Avicennia marina in the Central of the Red Sea, about half that for N and P. The comparatively low efficiency in iron resorption, compared to N and P resorption helps explain experimental results reporting that iron additions resulted in significantly taller plants compared with complete fertilizer additions, and consistent with the biogenic nature of the sediments in the Red Sea (Almahasheer et al, 2016b), similar to the iron deficiency of seagrass growing above carbonate sediments reported in the Mexican Caribbean (Duarte et al, 1995). These results also support the findings of a mesocosm experiment (Alongi, 2010) reporting that mangroves growth in some forests may be limited by the rate at which iron is solubilized by iron-reducing bacteria. Particularly when considering the high sediment Fe stock in this study of 1 Kg m −2 compared to around 0.1 Kg m −2 for N and P respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, iron has also been found to be limiting (Alongi, 2010;Almahasheer et al, 2016b), and it has been suggested that the low availability of the three elements may be the reason for mangroves absence in several coastlines otherwise having conditions suitable for mangrove growth (Sato et al, 2011). Nutrient resorption may be, therefore, a key strategy for mangroves to grow in oligotrophic environments, such as the Red Sea (Almahasheer et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of iron-limited growth of Central Red Sea seedlings is consistent with (Alongi, 2010), who reported high iron requirements in the transition stage from seedling to sapling in five mangrove species growing in north Queensland, Australia. Iron limitation in mangrove growth in the Central Red Sea is expected, as iron limitation is characteristic of marine coastal habitats dominated by biogenic carbonate sediments, which are typically iron depleted (Duarte et al, 1995).…”
Section: Nutrient Requirements and Critical Concentrationssupporting
confidence: 89%
“…The outcome of these experiments depend on location, with some mangrove stands shown to be limited by phosphorous (Feller, 1995;Koch and Snedaker, 1997;Feller et al, 2003a;Lovelock et al, 2004Lovelock et al, , 2006) and others to be limited by nitrogen (Feller et al, 2003b;Naidoo, 2009). Prior to the present study, iron limitation in mangrove growth had been reported, on the basis of experimental addition, only in mangroves in north Queensland, Australia (Alongi, 2010). The finding that mangroves in the Central Red Sea are nutrient-limited, as evidenced by low nutrient concentrations in their leaves and very low iron levels in the propagules they form, allows us to begin to understand the functioning and drivers of these important components of the Red Sea ecosystem.…”
Section: Nutrient Inputs To the Red Seamentioning
confidence: 65%
See 1 more Smart Citation